A novel porous rod with nanosphere CuS2/NiFe2O4 nanocomposite for low-cost high-performance energy storage system - Manzoor, Sumaira; Alburaih, H. A.; Nisa, Mehar Un; Aman, Salma; Abdullah, Muhammad; Abid, Abdul Ghafoor (Journal of materials science. Materials in electronics, 2023)
Spinel ferrites have lately gained popularity owing to their unique properties like high electrochemical stability, redox states & pseudocapacitive activity for supercapacitors applications. In present study, firstly rationally designed CuS 2 /NiFe 2 O 4 nanostructure is fabricated using a simple and efficient single step hydrothermal route. The resultant CuS 2 /NiFe 2 O 4 outperforms the capacitance efficiency of the CuS 2 and NiFe 2 O 4 due to the synergistic effect. The CuS 2 /NiFe 2 O 4 nanocomposite responses greater specific capacitance of 1329.54 F g −1 at 1.0 A g −1 , & nanocomposite electrode employed more than 96.21% of its capacitance around 5 A g −1 even after 5000 cycles. Hence, electrochemical efficiency could be boast up by tailoring in the morphology, surface interfaces and creation of oxygen vacancy. Therefore, this hybrid material might also be employed for water splitting catalysts, Na-ion hybrid capacitors, and other difficult energy storage and conversion devices.